FATHER’S ROLE AND CHARACTER EDUCATION: A REFLECTIVE ANALYSIS OF THE QUR’ANIC STORIES - Bahri, Samsul; Thahira, Yasmin; Taqwadin, Danil Akbar (Universitas Islam Negeri Ar-Raniry, 2024)
The Qur'an as a source of guidance accommodates various factors that can guide humans towards achieving worldly and hereafter benefits. Not all the guidance of the Qur'an are explicitly expressed in the form of understandable and practical commands and prohibitions. Some of the instructions from the Qur'an are obtained by interpreting certain symbols, including through the stories of the previous populaces. This study aims to explore the role of fathers in educating children's character through the five stories of father and son in the Qur'an, namely the story of Prophet Abraham, Prophet Jacob, Prophet Noah, Sheikh Madyan and Luqmān. This study adopts a qualitative methodology by adhering to the thematic interpretation (mauḍūʿī)) pattern with a tarbawī (an Islamic education approach) pattern method of analysis. The data of this paper were obtained in the form of verses of the Qur'an and their interpretations as well as other written materials and presented qualitatively after going through a number of analyses and interpretations. The results of the study conclude that the Qur'an clearly describes the role of father figures in educating children's character. These figures educate children's character by instilling monotheism; determination to maintain faith, worship and morals; be a good listener; understand the character of the child; be democratic and respect children's opinions; and are patient even if the child disobeys.